Retrospective review of chest trauma in Hospital Universiti Sains Malaysia over 10-year period - Mokhtar, Mohd Faris (2014)

(untitled)
BACKGROUND: Chest trauma is an important trauma globally accounting for about 10% of trauma admission and 25% of trauma death. Different types and severity of chest trauma in different subsets of patients with varying associated injuries result in different outcomes. OBJECTIVE: To study the pattern, aetiology, management, and outcome of chest trauma in Hospital Universiti Sains Malaysia (HUSM) over 10-year period from January 2003 till December 2012. METHODS: This is a 10-year retrospective study, which was conducted in HUSM from January 2003 till December 2012. It involved 504 patients who were admitted to surgical ward HUSM during the study period. The hospitalization criteria include intra-thoracic injury and clinically significant rib cage injury. Exclusion criteria for this study include patients who arrived dead in the emergency room, patients who did not complete their treatment in our hospital, isolated laryngeal or spinal injuries, oesophageal and tracheal injuries due to foreign body swallowing or aspirating and non-traumatic injuries to the chest (burns, electrical shocks, etc). The data was retrieved from medical record and analyzed concerning age, gender, comorbid, mechanism and aetiology of the trauma, thoracic and extra-thoracic injuries, intensive care unit (ICU) admission, mechanical ventilation, management, hospital length of stay (LOS) and mortality. RESULTS: A total of 504 patients met the inclusion criteria, where 412 were males (82.0%). The most frequent aetiology was road traffic accident (RTA) (425 cases; 84.3%). The most frequent type of chest trauma was rib fracture (384 cases; 76.2%). The risk for associated intrathoracic injuries increased significantly as the number of rib fracture increase. There were 11 (2.2%) thoracotomies performed during the study period where 8 of them were caused by penetrating injury. Overall hospital length of stay (LOS) ranged from 1-94 days with mean of 10.2 days (SD=12.4). Mortality was observed in 35 patients (6.9%). Associated extrathoracic injuries, ICU admission and ventilation requirement were significantly affect hospital LOS and mortality. CONCLUSIONS: RTA is the main cause of chest trauma in Kelantan. The number of rib fractures more than 5 is a good indicator of the severity of the injury. Presence of extrathoracic injuries, ICU admission and ventilation requirement have been found to be a good predictors for outcome of chest trauma.